Entamoeba dispar: A Rare Case of Enteritis in a Patient Living in a Nonendemic Area - Rosalia Graffeo; Carola Maria Archibusacci; Silvia Soldini; Lucio Romano; Luca Masucci (Case Reports in Gastrointestinal Medicine)
Entamoeba dispar, a common noninvasive parasite, is indistinguishable in its cysts and trophozoite forms from Entamoeba histolytica, the cause of invasive amebiasis, by microscopy. To differentiate the two species seems to be a problem for laboratory diagnosis. Recent experimental studies showed that  E. dispar can be considered pathogenic too. We present a rare case of enteritis due to E. dispar.